Occupational bladder cancer: Polymorphisms of xenobiotic metabolizing enzymes, exposures, and prognosis. Issue 7 (18th April 2017) - Lukas, Cordula; Selinski, Silvia; Prager, Hans-Martin; Blaszkewicz, Meinolf; Hengstler, Jan G.; Golka, Klaus
ABSTRACT: Approximately 7% of all bladder cancer cases in males are associated with occupation. The question arises whether the use of genome-wide association studies was able to identify bladder cancer risk factors that may modulate occupational bladder cancer risk and prognosis. One hundred and forty-three bladder cancer cases with suspected occupational bladder cancer and 337 controls were genotyped for the following polymorphisms: N-acetyltransferase 2 (NAT2), glutathione S-transferase M1 (GSTM1), glutathione S-transferase T1 (GSTT1), UDP-glucuronyltransferase 1A rs11892031 (UGT1A), rs9642880 (close to c-MYC), and rs710521 (close to TP63). The most relevant polymorphisms for occupational bladder cancer risk were GSTM1 and UGT1A, especially when co-occurring (GSTM1 negative and rs11892031[A/A]: 48% cases vs. 38% controls, OR 1.47, 95% CI 0.99–2.20). The effect was more pronounced in smokers. GSTM1 negative genotype occurred more frequently in cancer cases exposed to aromatic amines, carbolineum, and in painters and varnishers. UGT1A (rs11892031[A/A]) was found frequently in cases exposed to carbolineum, crack test spray, PAH, and in painters and varnishers. All investigated polymorphisms except rs710521 (TP63) seemed to exert an impact on recurrence risk. Relapse-free times were shorter for NAT2 slow and ultra-slow, GSTT1 positive and GSTM1 negative cases. Occupational bladder cancer cases with a number of risk variants displayed significantly shorter relapse-free times compared to cases with few, less relevant risk alleles as evidenced by median difference 8 months. In conclusion, in the present, suspected occupational bladder cancer cases phase II polymorphisms involved in bladder carcinogen metabolism modulate bladder cancer recurrence. Most relevant for bladder cancer risk were GSTM1 and UGT1A but not NAT2.